2015
DOI: 10.5937/leksir1535037m
|View full text |Cite
|
Sign up to set email alerts
|

Mulching as a physical weed control method applicable in medicinal plants cultivations

Abstract: Physical methods for weeds suppression in cultivation encompass many methods but our article focuses on application of various mulches. They belong to integrated non-chemical weed management strategies and are very useful in organic farming. Mulching might be performed either by the use of biodegradable mulching materials or by various mulch films. The main benefits of organic mulches are that they can be collected from the nature, thus providing cheaper crop production. In addition, they use to be biodegradab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…Used black "agrotextil" permeable film proved to be effective in preserving moisture and also in controlling weeds. Studies done on peppermint confirmed effectiveness of black "agrotextil" permeable film on yield and weed reduction (Matković et al, 2015). Positive effect in use of plastic mulch films on medicinal crops was reported in other studies conducted in our country as well (Radanovic et al, 2007;2016).…”
Section: Yield Per Single Plantsupporting
confidence: 75%
See 1 more Smart Citation
“…Used black "agrotextil" permeable film proved to be effective in preserving moisture and also in controlling weeds. Studies done on peppermint confirmed effectiveness of black "agrotextil" permeable film on yield and weed reduction (Matković et al, 2015). Positive effect in use of plastic mulch films on medicinal crops was reported in other studies conducted in our country as well (Radanovic et al, 2007;2016).…”
Section: Yield Per Single Plantsupporting
confidence: 75%
“…In order to avoid application of herbicides, alternative weed control methods are preferable. Physical methods, such as mulching, provide better conditions for cultivated crop as they reduce weeds and influence soil moisture, temperature and structure (Radanovic et al, 2016;Matković et al, 2015). In addition, dry farming conditions, which frequently include extreme environmental conditions (drought, high summer or low winter temperatures, strong wind, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Mulching is one of the most appropriate physical methods for weed control [Matković 2017]. Plant residues, such as straw, grass, or cover crops, and peat, used for mulching can suppress weeds and decrease weed infestation [Arentoft et al 2013, Kosterna 2014a, b, Kumar et al 2014, Błażewicz--Woźniak et al 2015, Thankamani et al 2016, prevent weed seed germination and growth due to release of phytotoxic substances during plant residue decomposition [Putnam et al 1983, Schilling et al 1985, Blum et al, 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Weed infestation during the critical periods (between 30 and 75 days in the first harvest, and 15 and 45 days in the second one) in cultivation of Mentha arvensis L. caused significant reduction in plants height, herb and oil yields [6]. Therefore, principals of organic production [7] and application of acceptable alternative methods in weed control are highly recommended [8,9]. Weeds suppression with application of physical method, such as mulching [9,10] prove to have positive effects in so many ways [8,[11][12][13][14][15][16]; the main ones are reduction in weedness [14,17,18] with significantly lower weed biomass [19], and possibility to change weed composition in accordance to ecological conditions [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, principals of organic production [7] and application of acceptable alternative methods in weed control are highly recommended [8,9]. Weeds suppression with application of physical method, such as mulching [9,10] prove to have positive effects in so many ways [8,[11][12][13][14][15][16]; the main ones are reduction in weedness [14,17,18] with significantly lower weed biomass [19], and possibility to change weed composition in accordance to ecological conditions [20]. In addition, mulching positively influences the soil moisture, structure and temperature [21][22][23], providing better conditions for cultivated plant.…”
Section: Introductionmentioning
confidence: 99%